Blending family therapy modalities: creating structure through play. Issue 4 (20th October 2022) - Mehta, Anita; Burley, Sarah
ABSTRACT: The success of family therapy is contingent on a thorough family assessment. Even more critical is the determination of an appropriate treatment plan. There are many differing treatment modalities, a therapist can explore and integrate to form the most effective interventions. This article will use a case study to describe the family of a little girl with ADHD, being raised in two homes by divorced parents. Their constant dispute created a chronic attachment rupture that required the blending of multiple therapeutic modalities. The therapeutic interventions of Theraplay® and structural family therapy will be described and the clinical relevance and application to this family will emphasize its value. Outcomes of this integrative approach included increased maternal insight, participation in play activities, increased ability to implement structure in the home, and behavioral changes in the child. Finally, recommendations on the importance of integrating Theraplay® with other modalities for family therapists will be highlighted.